Conflict dynamics in post-2011 Libya: a political economy perspective. Issue 5 (2nd September 2016) - Costantini, Irene
Abstract: After the fall of the Qadhafi regime Libya has become a theatre of conflict and violence. In the midst of the vacuum left by the sudden collapse of the old regime, various groups have come to contest their role in a new Libya. Illicit trafficking and the exploitation of oil resources have contributed to this struggle by empowering certain actors over others and by exhausting the capacity of the state. This article investigates the derailing of the Libyan transition and the opening of a new phase of conflict from a political economy perspective. It engages with key arguments developed in the literature on the economic causes of war and shows that the conflict in Libya challenges some of their conclusions. The establishment of areas of de facto sovereignty—warlordism—suggests two key factors explaining the discrepancy between theoretical arguments and empirical evidence: the problematic and contested definition of state and non-state actors in Libya; and an emerging political economy which is best described as an overproduction of governance rather than a lack of it.